Genetic Population Structure of Jumbo Squid ( Dosidicus gigas ) in the Southeastern Pacific Ocean and Its Implication for Fisheries Management - M. Cecilia Pardo‐Gandarillas; Pamela Morales; Jennifer Catalán; Sergio A. Carrasco; Sebastián Hernández; Pablo A. Oyarzún; Rodrigo Wiff; Christian M. Ibáñez (Fisheries Management and Ecology, 2025)
Species with high connectivity usually lack genetic differentiation. We tested for the presence of multiple populations of jumbo squid ( Dosidicus gigas ) on the Southeastern Pacific Ocean. Samples were collected from Ecuador to southern Chile (1.5° S–38° S). Two mitochondrial genes were sequenced (COI and ND2). Jumbo squids from all sampled locations in Ecuador, Peru, and Chile, as a whole, were characterized by low genetic diversity and an absence of spatial genetic structure, which suggest the presence of a population genetic unit in the Southeastern Pacific Ocean. Absence of spatial genetic structure was associated with high vagility of adults, eggs, and paralarvae of jumbo squid. We conclude that jumbo squid should be managed as a single biological stock along the Southeastern Pacific Ocean.